Efektivitas Penggunaan Aplikasi Sistem Integrasi Sekreariat dan Unsur Penunjang (Si-SEKRUP) di Lingkup Diskominfo Provinsi Jawa Tengah - Hendri Prasetyo; Fitria Nur 'Aini (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Digital transformation in government governance demands an integrated information system capable of increasing efficiency, transparency, and accountability. This study aims to analyze the effectiveness of the use of the Secretariat and Supporting Elements Integration System Application (Si-SEKRUP) at the Communication and Informatics Office of Central Java Province. The research method used a qualitative descriptive approach with data triangulation techniques in the form of documentation, observation, and literature studies. The results of the study indicate that the implementation of Si-SEKRUP has a positive impact on administrative management. This application is able to accelerate administrative processes by up to 50% compared to the previous manual system. In addition, electronic document recording encourages transparency, while digital and real-time asset monitoring strengthens institutional accountability. Resource efficiency has also increased, as seen from the significant reduction in paper use, in line with the principles of green office. The research findings are linked to the theory of organizational effectiveness and Management Information Systems (MIS), where Si-SEKRUP is assessed to have met the indicators of accuracy, timeliness, relevance, and efficiency of information. This indicates that the application can function as a supporting tool in strategic and operational decision-making within government organizations. However, optimizing the application's use still faces challenges, particularly related to the need for employee training and consistent managerial support. With strengthened human resource capacity and leadership commitment, Si-SEKRUP has the potential to become an effective and sustainable integrated information system model supporting digital-based bureaucratic reform.